Motor Performance in Children and Adolescents with Attention Deficit and Hyperactivity Disorder: A Systematic Review - Farias-Valenzuela, C; De Moraes-Ferrari, G; Castillo-Paredes, A; Garces-Rivas, N (American Institute of Mathematical Sciences, 2025)
Attention deficit hyperactivity disorder (ADHD) manifests itself in inattention, impulsivity, and/or hyperactivity. Those affected with ADHD have high motor coordination or motor performance problems, which presents as a daily difficulty. On the other hand, physical activity can produce motor benefits and ADHD symptomatology. Therefore, the aim of this systematic review is to analyze the effects of physical activity, sport, exercise, play or physical education interventions on the motor performance of children and adolescents with ADHD (registry: INPLASY202370105). The databases PubMed (87), Scopus (133), WoS (126), and SciELO (0) were searched using the keywords "Children" OR "Adolescent" AND "ADHD" OR "attention-deficit/hyperactivity disorder" OR "attention deficit hyperactivity disorder" AND "Motor skills" OR "Motor coordination" OR "Motor Performance" OR "Motor impairment" AND "Physical activity" OR "Exercise" OR "Sports" OR "Physical Education" OR "Play" OR "Pretend play". 14 studies met the inclusion criteria. The PEDro scale and risk of bias were used to evaluate the methodological quality of the selected articles. Benefits were evidenced in motor skills, cognitive functions, executive functions, and academic and social performance in children and adolescents with ADHD.